Gender and climate experts explore and share insights from case studies that utilize socio-technical innovation bundles (STIBs) in India - CGIAR Gender Equality Initiative (CGIAR Initiative on Gender Equality, 2024)
CGIAR GENDER Impact Platform and CGIAR Gender Equality initiative, HER+ began the year with a webinar focused on socio-technical innovation bundling to strengthen women’s resilience to climate change: distilling learnings from case studies. This webinar held on January 25 presented insights on various case studies where STIBs have contributed to women’s empowerment and resilience and learn from them as we are piloting STIBs in multiple learning labs across the globe.